Design of a Low-Profile Dual Linearly Polarized Antenna Array for mm-Wave 5G - Marco Simone; Santi Concetto Pavone; Matteo Bruno Lodi; Nicola Curreli; Giacomo Muntoni; Alessandro Fanti; Gino Sorbello; Giuseppe Mazzarella (IEEE Access, 2023)
This work proposes a dual linearly polarized antenna array for 5G mm-wave band, which is designed to be compatible with planar printed circuit board technology. The proposed antenna is engineered with a focus on simplifying the antenna geometry and eliminating any critical issues that may arise in antenna manufacturing. The proposed antenna has been evaluated, finding a 7% impedance bandwidth centered around 27.28 GHz. Additionally, the beam steering capability of the antenna is found to cover a ±30% angular width for both linear polarizations. These findings highlight the potential of the proposed antenna for use in 5G mm-wave band applications, where compatibility with planar printed circuit board technology and simplified antenna geometry are essential design requirements.